ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTATION FOR CHILDREN WITH HEMOPHAGOCYTIC SYNDROME: SINGLE CENTER EXPERIENCE - Ozturk, G.; Akcay, A.; Erbey, F.; Atay, D. (FERRATA STORTI FOUNDATION, 2015)
20th Congress of European-Hematology-Association, Vienna, AUSTRIA, JUN 11-14, 2015